The Influence Of Pre-Operative Health Education To The Self-Concept Improvement On Femoral Fracture Patientsat Haji Medan Hospital Of North SumateraGovernment In 2021 - Marniati; Sri Misleini; Zuidah (International Journal of Science, Technology & Management, 2021)
Femoral fracture is continuity disconnected of the femoral shaft occurring due to direct trauma (traffic accidents, falls from the height), and it is usually experienced by the adult males. Fractures of this area affects heavy bleeding and impacts the shock. This study aimed to find out whether there is the influence of pre-operative health education to the self-concept improvement on femoral fracture patients At Haji Medan Hospital of North Sumatera Government in 2021The research type used was Quasi Experiment design. This study used one group pre-test and post-test design. The research location was at Haji Medan Hospital of North Sumatera Government in 2021. The population were all femoral fracture patients having treatment at Haji Medan Hospital of North Sumatera Government. Based on RSU Haji Medical record data, there were 30 patients in July- December 2020. The sampling technique was purposive sampling. The total sample were 20 femoral patients.The outputs described that there is a significant correlation between pre operative health education and self-concept improvement on femoral fracture patients At Haji Medan Hospital of North Sumatera Government in 2021. The value is p < ? as 0.000 < 0.05. It is proved that pre operative health education to be effective in improving self-concept on femoral fracture patients At Haji Medan Hospital of North Sumatera Government in 2021.The suggestion of the study is required to be applied by medical practitioner in the hospital, particularly the nurses providing the nursing care to the femoral fracture patients and support the patients in overcoming the anxiety of the disease by maximizing the existing social supports.